(untitled) (Economics and region, 2023)
The study highlights the importance of developing applied tools to assess the economic impact of the development of corporate entrepreneurship within established business organisations. It was found that preliminary studies focus on the positive impact of the application of the entrepreneurial management style on the performance of business organisations, but there is a lack of specific proposals for assessing the impact of the implementation of employees’ internal business initiatives on organisational performance. The financial model for assessing the economic impact of the implementation of innovative solutions, ideas and projects proposed by employees and the creation of new business units based on them has been substantiated. The results of the authors’ calculations are presented, which confirm the practical possibility of applying the proposed model and demonstrate the positive impact of the development of corporate entrepreneurship and the creation of new business units on the value of the business organisation as a whole.